1999
DOI: 10.1093/oxfordjournals.aje.a009934
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Heart Rate during an Air Pollution Episode

Abstract: This paper assesses whether air pollution increases resting heart rates in 2,681 men and women aged 25-64 years who participated in the MONICA (monitoring of trends and determinants in cardiovascular disease) Augsburg cohort. Increases in heart rate were observed during the air pollution episode in January 1985 compared with non-episode days adjusted for cardiovascular risk factors and meteorologic parameters. Consistently, heart rates were also elevated at high concentrations of sulfur dioxide, total suspende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
121
4
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(143 citation statements)
references
References 30 publications
13
121
4
5
Order By: Relevance
“…This value is higher compared to those of healthy 22 -to 24 -year-old adults (HR: 57 -61 beats /min ) ( Hausberg et al, 1997 ) and elderly subjects ages 65 -89 ( HR: 65 -81 beats /min ) (Liao et al, 1999 ). Our analyses indicated nonsignificant positive effect estimates relating ambient PM and HR, which compare well with other studies reporting positive relationships (Peters et al, 1999;Pope et al, 1999a,b ). The sizes of the effect estimates for our data, however, were larger, indicating that a 100 g/m 3 increase in PM 10 would lead to a 6 beats / min increase in HR.…”
Section: Cardiovascular Health Endpointssupporting
confidence: 78%
“…This value is higher compared to those of healthy 22 -to 24 -year-old adults (HR: 57 -61 beats /min ) ( Hausberg et al, 1997 ) and elderly subjects ages 65 -89 ( HR: 65 -81 beats /min ) (Liao et al, 1999 ). Our analyses indicated nonsignificant positive effect estimates relating ambient PM and HR, which compare well with other studies reporting positive relationships (Peters et al, 1999;Pope et al, 1999a,b ). The sizes of the effect estimates for our data, however, were larger, indicating that a 100 g/m 3 increase in PM 10 would lead to a 6 beats / min increase in HR.…”
Section: Cardiovascular Health Endpointssupporting
confidence: 78%
“…Other researchers have recently reported similar associations between airborne particulate matter and increased pulse rate ( Peters et al, 1999;Pope et al, 1999a ) , decreased HRV (Pope et al, 1999b ), and occurrence of cardiac arrhythmia ( Peters et al, 2000 ).…”
Section: Introductionmentioning
confidence: 73%
“…Peters et al (1999) documented an association between increase in HR and an air pollution episode in Germany. However, direct comparisons of our results for Ni and HR to those of previous studies may not entirely appropriate because the differences in exposure metric (PM 2.5 vs Ni), and differences in study populations (coronary artery disease vs COPD).…”
Section: Issues In Health Effects Assessmentmentioning
confidence: 99%
“…In population-based studies, Peters et al (1999) reported increased HR during an air pollution episode, and Pope et al (2004) reported changes in HRV with ambient PM concentration.…”
Section: Introductionmentioning
confidence: 99%